Structural health monitoring II : selected, peer reviewed papers from the Second International Conference on Smart Diagnostics of Structures, November 14-16, 2011, Cracow, Poland - Uhl, Tadeusz (Key engineering materials, 2012)
The aim of this special collection is to bring together the expertise of scientists and engineers from universities and industry who work in the fields of Structural Health Monitoring, Non-Destructive Evaluation and Condition Monitoring. Networking between diagnostic systems designers and system users is crucial to the successful operation of many SHM systems. The study of damage detection, localization and assessment are important to the rapidly growing area of SHM. Review from Book News Inc.: This volume collects 45 papers from the Second International Conference on Smart Diagnostics of Structures, held in Krakow, Poland, in November of 2011. Academic and industry scientists and engineers from Europe, Australia, and Tunisia working in mechanics, materials engineering, electronics, software engineering, and signal processing, as well as system users from civil engineering, aviation, power plants, wind turbines, chemical and petrochemical plants, and railways sectors address the fields of structural health monitoring, non-destructive evaluation, and condition monitoring, in addition to advanced measurement techniques, signal processing theory and applications, and computation methods. Papers also cover the general theory of technical diagnostics; sensor and measurement systems in diagnostics; analytical and numerical models of technical facilities and their application in diagnostics; algorithms, methods, and diagnostic tools; rotating machinery diagnostics; methods of detection, location, and assessment of failures; artificial intelligence in diagnostics; diagnostics of industrial and mechatronic systems; machineries and industrial systems health management; and economic aspects of technical diagnostics.